THE INFLUENCE OF BRAND IMAGE, PRODUCT QUALITY, AND PRICE ON DECISION TO BUY SAMSUNG SMARTPHONES (CASE STUDY ON EMPLOYEES OF PT ANGKASA PURA AVIASI KUALANAMU INTERNATIONAL AIRPORT) - Akhmad Syarif Sinaga; Arlina Nurbaity Lubis; Beby Karina Fawzeea Sembiring (RADJA PUBLIKA, 2024)
The rapid development of digital technology has given the impact on the increase in demands for various kinds of communication devices which causes the high competition in attracting market segments in communication. Many smartphone businesses compete tightly in the national and international markets, offering various products with unique features to help consumers in their activities. Decision to buy is when buyers have decided to determine their choices and bought certain products. The objective of the research was to find out ad analyze the influence of brand image, product quality, and price on decision to buy Samsung smartphones. The research subjects were 544 employees of PT Angkasa Pura Aviasi of Kualanamu International Airport who had bought and used Samsung smartphones, and 108 of them were used as the samples. The data were gathered by distributing questionnaires and analyzed using multiple linear regression analysis. The result of the research showed that, simultaneously, brand image, product quality, and price had a significant influence on decision to buy Samsung smartphones made by the employees of PT Angkasa Pura Aviasi of Kualanamu International Airport. Partially, brand image, product quality, and price respectively had positive and significant influence on decision to buy Samsung smartphones made by the employees of PT Angkasa Pura Aviasi of Kualanamu International Airport. It was found that brand image had the most dominant influence on the decision to buy Samsung smartphones by the employees of PT Angkasa Pura Aviasi of Kualanamu International Airport